Determinación de perfil lipídico: triglicéridos, colesterol, lipoproteínas de alta densidad - HDL, lipoproteínas de baja densidad - LDL, en la Comuna de Quera Alto del cantón Chilla de la provincia de El Oro en el primer trimestre del año 2012 - Ganán Ordóñez, Jinson F. (2012)
The present investigation has developed in the community of Quera Alto of the canton Chilla, that is located lacking of basic services such as water supply, sewerage and health centers, has for this reason developed this research entitled: Determination lipid profile: triglycerides, cholesterol, high density lipoprotein-HDL, low-density lipoprotein-LDL, in the commune of Quera Alto of the province of El Oro in the first quarter of 2012.